2H-Azirines as electrophiles - Alves, M. José (2011)
2H-Azirines have shown an unusual potential to synthesise aziridines and other types of compounds. Many functionalized aziridines can be produced by addition of O-, S-,N-, C-nucleophiles and hydride to 2H-azirines. This review is designed to give an overview of the reactivity of 2H-azirines as electrophiles along the years and their usefulness in the synthesisof important families of compounds.